Cinema's Queer Witness: Ira Sachs's Last Address and the Indifferent View - Rodness, Roshaya (CR: The New Centennial Review, 2019)
Roshaya Rodness is a senior doctoral candidate in the Department of English and Cultural Studies at McMaster University. Her dissertation addresses recent movements in queer theory with a special focus on cinema, poststructuralist ethics, and the nonhuman. She has published in Canadian Literature, Chiasma: A Site for Thought , and World Picture on topics that include contemporary film, indigenous authorship, postcontinental philosophy, and dream theories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; _Nettoyé